Caregivers’ responses to children’s negative emotions: Associations with preschoolers’ executive functioning - Fernandes, C. (2022)
There is a lack of knowledge regarding the connection between parental emotional responsiveness and children’s executive functioning (EF). This study aimed to explore the relations between caregivers’ reactions to their children’s distress and children’s EF. Mothers of 136 preschoolers reported their reactions to their children’s negative emotions using the Coping with Children’s Negative Emotions Scale. Children’s EF was assessed through the mothers and teachers’ reports using the Behavioral Inventory of Executive Functioning for Preschool Children. Results showed that the mothers’ perceived use of negative emotional regulation responses (i.e., punitive and minimizing reactions) was associated with lower levels of EF in children, as reported by both mothers and teachers. The association between the mothers’ use of positive emotional regulation responses (i.e., problem-focused, emotion-focused, and expressive encouragement reactions) and children’s EF was not significant. Multiple regression analyses revealed that the mothers’ use of negative emotional regulation responses accounted for significant proportions of variance in EF indexes. These findings suggest that parental socialization of emotion could be important for children’s EF. Specifically, caregivers’ negative emotional regulation responses to children’s distress may serve as a risk factor for poorer EF in children. Efforts to improve children’s EF may be more effective when parental emotional responsiveness to their distress is considered.